2023
DOI: 10.1002/pro.4711
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the inhibitory property of DM hCT on hCT fibrillization via its relevant peptide fragments

Abstract: The irreversible aggregation of proteins or peptides greatly limits their bioavailability; therefore, effective inhibition using small molecules or biocompatible materials is very difficult. Human calcitonin (hCT), a hormone polypeptide with 32 residues, is secreted by the C-cells of the thyroid gland.The biological function of this hormone is to regulate calcium and phosphate concentrations in the blood via several different pathways. One of these is to inhibit the activity of osteoclasts; thus, calcitonin co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…The enhanced stability of the dynamic helix in DM-hCT compared to hCT was consistent with the CD measurements. 16,23 Overall, our analysis of residue-pairwise contacts indicated that the Y12L and N17H mutations stabilize the dynamic helical conformations, thus contributing to the suppression of the conformational transition from helix to β-sheet in the hCT monomer.…”
Section: Resultsmentioning
confidence: 75%
See 4 more Smart Citations
“…The enhanced stability of the dynamic helix in DM-hCT compared to hCT was consistent with the CD measurements. 16,23 Overall, our analysis of residue-pairwise contacts indicated that the Y12L and N17H mutations stabilize the dynamic helical conformations, thus contributing to the suppression of the conformational transition from helix to β-sheet in the hCT monomer.…”
Section: Resultsmentioning
confidence: 75%
“…Future improvements to enhance DM-hCT's amyloid-resistance should focus on minimizing mutations to effectively reduce the remaining β-sheets. In conclusion, our simulations suggest that the experimentally determined amyloid-resistant Y12L and N17H substitutions 16,23 are achieved by stabilizing the dynamic helical conformation and suppressing its conversion to β-sheet structures. Our findings not only elucidate the molecular mechanism behind hCT aggregation and the amyloid-resistant effects of Y12L and N17H double substitutions but also offer valuable insights for developing next-generation hCT analogs for clinical applications.…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations